Outer membrane vesicles from bacteria: Role and potential value in the pathogenesis of chronic respiratory diseases - Han, Fei; Wang, Weiwei; Shi, Meng; Zhou, Hao; Yao, Yiwen; Li, Caiyun; Shang, Anquan (Frontiers in Cellular and Infection Microbiology, 2022)
Infectious diseases are the leading cause of death in both adults and children, with respiratory infections being the leading cause of death. A growing body of evidence suggests that bacterially released extracellular membrane vesicles play an important role in bacterial pathogenicity by targeting and (de)regulating host cells through the delivery of nucleic acids, proteins, lipids, and carbohydrates. Among the many factors contributing to bacterial pathogenicity are the outer membrane vesicles produced by the bacteria themselves. Bacterial membrane vesicles are being studied in more detail because of their potential role as deleterious mediators in bacterial infections. This review provides an overview of the most current information on the emerging role of bacterial membrane vesicles in the pathophysiology of pneumonia and its complications and their adoption as promising targets for future preventive and therapeutic approaches.